Актуальність реставрації парку садиби В. Липинського (с. Затурці Волинської області) - Reshetjuk, O. W.; Terletsky, W. C. (Національний дендрологічний парк "Софіївка" НАН України, 2021)
Park of W. Lypinsky estate in village Zaturtcy at Vohlyn region is relics of garden-park’s skill. But park’s modern condition hasn’t answered its primary structure. There has been directed the stock taking of present-day park’s state and putted together the plan of its restoration. Those work’s fulfillment would considerably expand the local potential of memorial Lypinsky estate’s museum and answer for standards of garden-park’s skills reservation.